2017
DOI: 10.1080/2162402x.2017.1377873
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21 combined with PD-1 or CTLA-4 blockade enhances antitumor immunity in mouse tumor models

Abstract: Recent advances in cancer treatment with checkpoint blockade of receptors such as CTLA-4 and PD-1 have demonstrated that combinations of agents with complementary immunomodulatory effects have the potential to enhance antitumor activity as compared to single agents. We investigated the efficacy of immune-modulatory interleukin-21 (IL-21) combined with checkpoint blockade in several syngeneic mouse tumor models. After tumor establishment, mice were administered recombinant mouse IL-21 (mIL-21) alone or in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…IL-21 was also found to induce PD-1 expression in T cells [36], what may be a potential explanation of our observed association of rs17388568 with anti-PD-1 sensitivity. Several studies have observed suggestive clinical efficacy of combined IL-21 and anti-PD-1 therapy in preclinical mouse models, which was correlated with elevated tumor infiltrated CD8+ T cells [37] and there are ongoing phase I clinical trials of anti-PD-1 and IL-21 for solid tumors [38]. While these and other evidence clearly point to a potential biological link between rs17388568 and IL-2/ IL21 genes in the locus, more detailed fine-mapping analysis of these associations will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…IL-21 was also found to induce PD-1 expression in T cells [36], what may be a potential explanation of our observed association of rs17388568 with anti-PD-1 sensitivity. Several studies have observed suggestive clinical efficacy of combined IL-21 and anti-PD-1 therapy in preclinical mouse models, which was correlated with elevated tumor infiltrated CD8+ T cells [37] and there are ongoing phase I clinical trials of anti-PD-1 and IL-21 for solid tumors [38]. While these and other evidence clearly point to a potential biological link between rs17388568 and IL-2/ IL21 genes in the locus, more detailed fine-mapping analysis of these associations will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…USA), who characterized a population of mesenchymal stem cells [145][146][147] that supports pancreatic tumor progression by releasing GM-CSF. 148 Moreover, (3) Hu and coauthors (from the University of Pennsylvania, Philadelphia, PA, USA) showed that CAR T cells engineered to secrete IL-18 mediate superior therapeutic responses in mice with B16F10 melanomas [157][158][159] as compared to CAR T cells with a wild-type secretory capacity 160 ; (4) Seo and co-workers (from Seoul National University, Seoul, Republic of Korea) demonstrated that IL-21 161 can be used to reverse NK cell exhaustion, at least mice, resulting in improved immunity against MHC Class I-deficient neoplasms 162 ; (5) Chapuis et al (from the Fred Hutchinson Cancer Research Center, Seattle, WA, USA) tested IL-21 primed CTLs transferred in combination with a CTLA4-targeting mAb to a single patient with metastatic melanoma refractory to either intervention alone, demonstrating robust tumor control, 163 mimicking preclinical results from independent investigators; 164 (6) Yin and collaborators (from Academia Sinica, Taipei, Taiwan) showed that the secretion of IL-25 [165][166][167] from cancer-associated fibroblasts [168][169][170][171][172] has direct oncosuppressive effects in preclinical models of breast carcinoma 173 ; and (7) Molgora et al (from the Humanitas Clinical and Research Center, Rozzano, Italy) reported that interleukin 1 receptor accessory protein like 1 (IL1RAPL1; best known as IL-1R8), a member of the IL-1b receptor protein family, [174][175][176][177][178] operates as an inhibitory checkpoint in the maturation of and acquisition of effector functions by NK cells. 179 These and other emerging aspects of the cytokine biology have considerable implications for the immunotherapeutic management of cancer and a plethora of other conditions, including infectious and autoimmune disorders.…”
Section: Preclinical and Translational Advancesmentioning
confidence: 99%
“…In a mouse tumor model, accumulation of Tfh cells was noted in DLNs, along with a concomitant increase in IL-4 produced by these cells ( 92 ). On the other hand, recent studies have shown a beneficial role of IL-21 in cancer immunotherapy strategies ( 93 , 94 ), possibly by modulating CD8 T cell response ( 95 97 ). Therefore, Tfh cells could potentially support antitumor immunity in ways extending past the help they provide to B cells.…”
Section: Lymph Nodes In Neoplasmsmentioning
confidence: 99%